Inhabiting Difference across Religion and Gender: Displaced Women’s Experiences at Turkey’s Border with Syria - Dağtaş, Seçil (Refuge: Canada’s Journal on Refugees, 2018)
The global refugee crisis gives new urgency to questions of gender and religion in contexts of displacement. This article adopts and contributes to an intersectional feminist reading of gendered displacement by examining the daily lives of a diverse group of displaced Syrian women at the southern borderlands of Turkey, a country hosting the world’s largest population of refugees today. I argue that the vernaculars of hospitality and border crossings surrounding these women’s lives assemble gendered practices and religious discourses in ways that rework and transcend their citizenship and identity-based differences. These assemblages, moreover, derive significant insight from women’s labour and everyday networks at the local level, which often go unnoticed in public debates. Research that shifts focus from institutional governance to women’s everyday sociality allows intersectional feminists to capture the nuances of displaced women’s agency and the contingencies of their dwelling and mobility in the Middle East against the de-historicized representations of victimized refugee women.